Polymorphism rs2682818 participates in the progression of colorectal carcinoma via miR-618-TIMP1 regulatory axis - Wei Shao (Nature Portfolio, 2021)
Abstract Colorectal carcinoma (CRC) has a high morbidity and mortality. Current studies have confirmed a variety of microRNA polymorphisms were associated with tumor susceptibility, however, the mechanisms are still unknown. In this study, we were aimed to clarify how polymorphism rs2682818 participated in the progression of CRC. First of all, the differential expression of miR-618 was assessed by quantitative real-time polymerase chain reaction in CRC patients with different genotypes of polymorphism rs2682818, including homozygous (TT) genotype, homozygous (GG) genotype and heterozygous (TG) genotype. Secondly, plasmids carried miR-168 precursor sequences harboring rs2682818 (SNP type) or without rs2682818 (wild type) were transfected into 293T cells to verify that polymorphism rs2682818 affected miR-618 expression. Thirdly, CCK-8 assay, flow cytometry assay, transwell assay and mouse xenograft assay were performed to measure the biological functions of miR-618 in CRC. Fourthly, the candidate target genes of miR-618 which were predicted by bioinformatics tools were verified by luciferase reporter assay. Finally, in order to explain the potential molecular mechanisms, western blotting was performed to demonstrate the differential expression and phosphorylation of pathway related proteins. The results showed that miR-618 was down-regulated in colon cancer, especially in CRC patients with rs2682818 GG homozygous genotype. Higher expression of mature miR-618 occurred in patients with TT homozygous genotype, and these patients usually had a longer survival time. Moreover, miR-618 mimic obviously impaired the growth and invasion ability of CRC cells, and miR-618 mimic also remarkably promoted CRC cell apoptosis. Our luciferase experiments confirmed that TIMP1 was a target of miR-618 in CRC cells. Knockdown of TIMP1 also significantly inhibited the malignant cytological features of CRC, including malignant growth and invasion as well as apoptosis resistance. In summary, polymorphism rs2682818 participated in the progression of CRC via affecting the expression of mature miR-618 in CRC cells, and miR-618 inhibited the progression of CRC via targeting TIMP1expression.